UPAYA GASTRODIPLOMASI INDONESIA DI AUTRALIA TAHUN 2021-2023 - Kanza, Marselia; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Gastrodiplomacy has emerged as a strategic tool for nations to enhance their global image. By leveraging the power of food, countries can foster international relations and promote their cultural heritage. Successful cases of gastrodiplomacy can be observed in a number of nations where culinary has proved to be a major driver in cultural and economic interactions. Inspired by this success, Indonesia launched the Indonesia Spice Up The World program to showcase its rich culinary heritage and spices on the global stage, with a particular focus on the Australian market. This study examines Indonesia's gastrodiplomacy efforts through this program in Sydney between 2021 and 2023. Employing a qualitative research methodology, this study combined primary data collected from interviews with non-governmental actors, such as the Indonesia Gastronomy Network, and secondary data from literature reviews and documents. The theory of multi-track diplomacy serves as the theoretical framework for this research. By utilizing the four tracks of theory, namely government, NGOs, businesses, and diasporas, this study explores the initiatives undertaken to promote Indonesian cuisine in Sydney during 2021-2023. The implementation of multi-track diplomacy indicates its effectiveness in supporting Indonesia's gastrodiplomacy efforts through the Indonesia Spice Up The World program. Each track delivers a distinctive contribution to the program's four pillars: spices and processed foods, Indonesian restaurants, culinary promotion, Indonesia’s gastronomy destination. Through the combined efforts of the four tracks, Indonesia has effectively strengthened its image and appeal as a culinary destination in Sydney between 2021 and 2023. This study emphasizes the significance of multi-stakeholder collaboration in implementing Indonesia’s gastrodiplomacy initiatives. Keywords: Gastrodiplomacy, Multi-Track Diplomacy, Soft Power, Indonesian Cuisine, Sydney